(Trans)forming #MeToo: Toward a Networked Response to Gender Violence. Issue 3 (3rd July 2019) - Hsu, V. Jo
Abstract: Drawing from critical trans theory's methods of systemic analysis, this article examines how #MeToo's carceral politics have reinforced the exclusion and ongoing abuse of those most vulnerable to gender and state violence. The stories of many people of color, queer, transgender, poor, and/or disabled folks remain inarticulable within a retributive system that requires survivors to narrate themselves as "perfect victims." Adopting critical trans theory's emphasis on administrative violence, I connect the transformative visions of penal abolition with discourses on sexual violence. Focusing on the rhetorical strategies of incarcerated survivors and their defense committees, I demonstrate how these rhetors model forms of Rebecca Dingo's "networked arguments." In doing so, they offer a promising vision of how organizers and advocates can address the particularities of individual experience while also responding to and working collaboratively against oppressive social and state institutions.